A Study on the Walking Comfort of CITYWALK Routes in Historic Districts for the Elderly—Taking Beijing’s Qianmen Dashilan Area as an Example - Zhang, Tongbin; Gao, Yichen; Gao, Yufei; Wang, Lei (Journal of Progress in Civil Engineering, 2025)
As China’s population ages rapidly, CITYWALK—a leisurely urban exploration method advocating slow-paced experiences—has increasingly become a vital pathway for the elderly to engage with historical spaces and cultural memories within cities. Historic districts, with their rich cultural heritage, emerge as preferred destinations for senior tourism and daily activities. However, their complex spatial environments and inadequate service configurations pose practical barriers to accessibility for older adults. This study examines Beijing’s Qianmen Dashilan district, constructing a three-dimensional evaluation framework—“spatial accessibility, service adaptability, and technological friendliness.” It employs multi-source data methods including field surveys, behavioral observations, in-depth interviews, and spatial coupling analysis of point data to systematically identify key constraints on elderly pedestrians’ routes. Findings reveal shortcomings including discontinuous accessibility infrastructure, uneven distribution of rest facilities, insufficient service node coverage, and generational barriers in smart navigation systems. Guided by the “micro-renewal” concept, this study proposes a synergistic optimization strategy of “micro-renovation + soft services + lightweight technology”: integrating community and commercial resources to strengthen emergency response and humanistic care; designing lightweight guidance systems to lower technological barriers. This research aims to provide an actionable theoretical framework and practical paradigm for age-friendly design in the context of historic district renewal, advancing the inclusivity and accessibility of urban public spaces.